2019
DOI: 10.1155/2019/1321973
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Suppresses Epithelial-Mesenchymal Transition in GBM by Regulating Smad-Dependent Signaling

Abstract: Glioblastoma (GBM) is the most common and malignant intracranial tumor in adults. Despite continuous improvements in diagnosis and therapeutic method, the prognosis is still far away from expectations. The invasive phenotype of GBM is the main reason for the poor prognosis. Epithelial-mesenchymal transition (EMT) is recognized as a participator in this invasive phenotype. Resveratrol, a natural plant-derived compound, is reported to be able to regulate EMT. In the present study, we used TGF-β1 to induce EMT an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 65 publications
1
37
0
Order By: Relevance
“…The postoperative administration of resveratrol results in a significant prognosis amelioration of rat-advanced orthotopic glioblastoma by reducing growth, inducting apoptosis, and suppressing STAT3 signaling [96]. In addition, resveratrol blocks epithelial-mesenchymal transition in GBM by modulating Smad signaling [97].…”
Section: Resveratrol Effects On Central Nervous System Cancersmentioning
confidence: 99%
“…The postoperative administration of resveratrol results in a significant prognosis amelioration of rat-advanced orthotopic glioblastoma by reducing growth, inducting apoptosis, and suppressing STAT3 signaling [96]. In addition, resveratrol blocks epithelial-mesenchymal transition in GBM by modulating Smad signaling [97].…”
Section: Resveratrol Effects On Central Nervous System Cancersmentioning
confidence: 99%
“…EMT, a trans differentiation process converting epithelial cells into motile mesenchymal cells, is involved in the induction of multiple signaling pathways, and leads to cancer progression [24,25]. Previous studies have indicated that EMT is identified as a mechanism resulting in the invasive phenotype of GBM cells [26,27]. TGFβ signaling pathway plays an important role in regulation of EMT, and is activated in high-grade gliomas, leading to poor prognosis [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that EMT induction enhances viability via the stimulation of cancer stem cell markers such as Bmi1 and Sox2. By inhibition of the TGF-β/Smad axis, Res not only inhibits EMT and migration, but also interferes with the proliferation and survival of cancer cells [ 179 ]. So, Res can function as a potential modulator of EMT in cancer cells to negatively affect their proliferation and metastasis.…”
Section: Resveratrol and Tgf-β Signaling Pathwaymentioning
confidence: 99%